2021
DOI: 10.3389/fpls.2021.725338
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Chemotaxis and Motility Systems at Work in the Soil

Abstract: Bacteria navigate their way often as individual cells through their chemical and biological environment in aqueous medium or across solid surfaces. They swim when starved or in response to physical and chemical stimuli. Flagella-driven chemotaxis in bacteria has emerged as a paradigm for both signal transduction and cellular decision-making. By altering motility, bacteria swim toward nutrient-rich environments, movement modulated by their chemotaxis systems with the addition of pili for surface movement. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 140 publications
(223 reference statements)
2
31
0
Order By: Relevance
“…It is known for the renowned squid-vibrio symbiotic system that the Vibrio bacteria show chemotaxis in response to the host-derived chitin oligosaccharides ( Mandel et al, 2012 ). Similar chemotactic behavior has been observed for several species of Rhizobium bacteria toward the plant roots ( Aroney et al, 2021 ). Similarly, we hypothesize that algal metabolites in Hydra might be actively attracting the invasive species such as Legionella and altering the colonization niche to stop its further spread like “lure-and-kill” mechanism.…”
Section: Discussionsupporting
confidence: 82%
“…It is known for the renowned squid-vibrio symbiotic system that the Vibrio bacteria show chemotaxis in response to the host-derived chitin oligosaccharides ( Mandel et al, 2012 ). Similar chemotactic behavior has been observed for several species of Rhizobium bacteria toward the plant roots ( Aroney et al, 2021 ). Similarly, we hypothesize that algal metabolites in Hydra might be actively attracting the invasive species such as Legionella and altering the colonization niche to stop its further spread like “lure-and-kill” mechanism.…”
Section: Discussionsupporting
confidence: 82%
“…Bacterial motility is not crucial for the establishment of rhizobia-legume symbiosis, but it affects the ability of rhizobial strains to quickly colonise and infect host legume roots (revised by [28]), which might be an important feature in natural conditions where different rhizobial strains can compete for nodulating the same plant. Unfortunately, all the HH103 mutants tested in this study and shown to be impaired in surface motility are affected in genes with relevant symbiotic functions [16,17,19,20,53,61], which prevents gaining any knowledge about the putative relevance of genistein-induced surface motility for HH103 symbiotic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation and surface motility are opposite behaviours exhibited by bacteria living on surfaces [ 22 , 25 ]. Rhizobial motility is not essential for nodulation and nitrogen fixation but can influence nodulation efficiency and competitiveness by approaching bacteria to potential infection sites and/or facilitating their progression inside infection threads [ 26 , 27 , 28 ]. Several studies have shown that rhizobial mutants affected in flagella synthesis exhibit partial defects in symbiotic performance such as reduced ability for root colonisation [ 29 ], delayed nodulation and/or reduced competitiveness for nodulating host legumes [ 25 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worth mentioning, such a type of motility is also important in terrestrial systems. For instance, assisting the movement of species within diffusible hotspots in the soil [e.g., plant-root surfaces ( Aroney et al, 2021 ), fungal hyphae ( Pion et al, 2013 ), see below].…”
Section: Defining Microbial Dispersalmentioning
confidence: 99%